2019
DOI: 10.1016/j.compstruct.2019.02.092
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for the analysis of post-tensioned structures using a constitutive serial-parallel rule of mixtures: Large scale non-linear analysis

Abstract: The main purpose of this paper is to develop a reliable method based on a three-dimensional (3D) finite-element (FE) model to simulate the constitutive behaviour of reinforced concrete structures strengthened with post-tensioned or pre-stressed tendons well beyond the elastic domain. The posttensioned concrete is modelled as a composite material whose behaviour is described with the serialparallel rule of mixtures (S-P RoM) [1-3] and the nonlinear behaviour of each component is accounted for by means of plasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…In this test, the stress variation of the steel bars was caused by two factors, one was the relaxation of the steel bars, and the other was the creep characteristic of the glulam. Previous studies showed that the relaxation of the steel bars was not significant anymore when the initial stress of the prestressed steel bars was less than 0.5 times value of the ultimate tensile strength R y [26][27][28][29][30][31][32][33]. Since the maximum prestress applied in this study was 60 MPa < 0.5fu = 270 MPa, the stress variation caused by the relaxation of the steel bars was ignored, and it was considered that the stress variation of the steel bars was mainly caused by the creep of the glulam.…”
Section: Stress Variation Of Steel Barsmentioning
confidence: 99%
“…In this test, the stress variation of the steel bars was caused by two factors, one was the relaxation of the steel bars, and the other was the creep characteristic of the glulam. Previous studies showed that the relaxation of the steel bars was not significant anymore when the initial stress of the prestressed steel bars was less than 0.5 times value of the ultimate tensile strength R y [26][27][28][29][30][31][32][33]. Since the maximum prestress applied in this study was 60 MPa < 0.5fu = 270 MPa, the stress variation caused by the relaxation of the steel bars was ignored, and it was considered that the stress variation of the steel bars was mainly caused by the creep of the glulam.…”
Section: Stress Variation Of Steel Barsmentioning
confidence: 99%
“…This means that the relation between the strains and stresses in the material is non-linear and therefore, the constitutive models chosen for simulating the simple materials must include these effects. For concrete, for example, a model has been used which includes the phenomena of damage, simulated by means of its stiffness degradation due to nonadmissible stress levels [2,3,6,7,10,11]. And for the case of prestressing steel, the stress relaxation phenomena, that takes place along time due to its intrinsic viscosity, has been simulated using the generalised Maxwell viscoelastic model [2,3,7,10].…”
Section: Strategy Of Analysismentioning
confidence: 99%
“…The methodology used to simulate the composite materials of the containment is the before mentioned S-P RoM [2,3,4,5,6,7]. This formulation is usually applied for the study of fiberreinforced composite materials and it defines two different behaviours in terms of the strain and the stress states of the composite constituent materials, i.e.…”
Section: Computational Model 41 Constitutive Modelling Of the Composite Materialsmentioning
confidence: 99%
See 2 more Smart Citations